Specific herbivore-induced volatiles defend plants and determine insect community composition in the field - Xiao, Y.; Wang, Q.; Erb, Matthias; Turlings, Ted; Ge, L.; Hu, L.; Li, J.; Han, X.; Zhang, T.; Lu, J.; Zhang, G.; Lou, Yonggen (My University, 2012)
In response to insect attack, plants release complex blends of volatile compounds. These volatiles serve as foraging cues for herbivores, predators and parasitoids, leading to plant-mediated interactions within and between trophic levels. Hence, plant volatiles may be important determinants of insect community composition. To test this, we created rice lines that are impaired in the emission of two major signals, S-linalool and (E)-beta-caryophyllene. We found that inducible S-linalool attracted predators and parasitoids as well as chewing herbivores, but repelled the rice brown planthopper Nilaparvata lugens, a major pest. The constitutively produced (E)-beta-caryophyllene on the other hand attracted both parasitoids and planthoppers, resulting in an increased herbivore load. Thus, silencing either signal resulted in specific insect assemblages in the field, highlighting the importance of plant volatiles in determining insect community structures. Moreover, the results imply that the manipulation of volatile emissions in crops has great potential for the control of pest populations.
Keywords: anagrus nilaparvatae; direct defence; genetic manipulation; herbivore-induced plant defence; indirect defence; nilaparvata lugens; plant-insect interactions; rice; tritrophic interaction; volatiles; anagrus-nilaparvatae; pest-management; rice; responses; attracts; enemies; caterpillar; complexity; induction; emissions